2020
DOI: 10.37934/arfmts.79.1.153168
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Improvement of Thermal Energy of Heat Exchangers with SWCNT, GQD Nanoparticles and PCM (RT82)

Abstract: Today, due to the reduction of energy resources in the world and its pollutants, energy storage methods and increase the thermal efficiency of various systems are very important. In this research, the thermal efficiency and energy storage of two heat exchangers have been investigated in series using phase change materials (RT82) and single wall carbon nanotubes (SWCNT) and graphene quantum dot nanoparticles (GQD) In this research, two heat exchangers have been used in combination. The first heat exchanger was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…On the other hand, fluid expansion in cylindrical chambers causes fluid circulation in the upper and lower part of the chamber, which itself is a reason for increasing the contact surface of the fluid and the wall, and as a result, increases the cooling performance of the system. 62…”
Section: Outlet and Overall Temperaturementioning
confidence: 99%
“…On the other hand, fluid expansion in cylindrical chambers causes fluid circulation in the upper and lower part of the chamber, which itself is a reason for increasing the contact surface of the fluid and the wall, and as a result, increases the cooling performance of the system. 62…”
Section: Outlet and Overall Temperaturementioning
confidence: 99%
“…Validation of numerical simulation of melting of the PCM was performed in the study. First, an initial run was performed and the predictions were compared with the experimental data of Hosseini et al [16] and Rostami et al [42], as shown in Figure 3. It is clearly noted in Figure 3 that a good agreement between the predictions and measured data was found.…”
Section: Numerical Procedures and Validationmentioning
confidence: 99%
“…Furthermore, the left and right points of the HTF demonstrate less melting. This is because the presence of side fins has prevented the natural convection due to PCM melting at the lower points of the heat transfer, while the highest amount of melting has occurred in the upper hemisphere of the heat transfer and between the two fins, which was due to the heat transfer from HTF Center [42][43][44][45]. Furthermore, with the increase of this process and heat circulation, it moves to the lower points.…”
Section: Effect Of Fin Tubes and Nanoparticles (Nano-htf) On The Pcm Melting Processmentioning
confidence: 99%
See 2 more Smart Citations